Highly grafted polystyrene/polyvinylpyridine polymer gold nanoparticles in a good solvent: effects of chain length and composition. Issue 15 (16th March 2016) - Posel, Zbyšek; Posocco, Paola; Lísal, Martin; Fermeglia, Maurizio; Pricl, Sabrina
Abstract : The structural features of spherical gold nanoparticles decorated with highly grafted poly(styrene) (PS), poly(vinylpyridine) (PVP) and PS–PVP diblock copolymer brushes immersed in a good solvent are investigated by means of DPD simulations as a function of grafted chain length and of copolymer chain composition. Abstract : In this work, the structural features of spherical gold nanoparticles (NPs) decorated with highly grafted poly(styrene) (PS), poly(vinylpyridine) (PVP) and PS–PVP diblock copolymer brushes immersed in a good solvent are investigated by means of Dissipative Particle Dynamics (DPD) simulations as a function of grafted chain length and of homopolymer and copolymer chain composition. For NPs grafted either by PS or PVP homopolymer brushes (selected as a proof of concept), good agreement between the Daoud–Cotton theory, experimental evidence, and our DPD simulations is observed in the scaling behavior of single chain properties, especially for longer grafted chains, and in brush thickness prediction. On the other hand, for grafted chain lengths comparable to NP dimensions parabolic-like profiles of the end-monomer distributions are obtained. Furthermore, a region of high concentration of polymer segments is observed in the monomer density distribution for long homopolymers. In the case of copolymer-decorated NPs, the repulsion between PS and PVP blocks is found to substantially influence the radius of gyration and the shape of the end-monomer distribution of the relevant polymer shell. Moreover, for diblock chains, the un-swollen region is observed to be thinner (and, correspondingly, the swollen layer thicker) than that of a NP modified with a homopolymer of the same length. Finally, the lateral segregation of PS and PVP blocks is evidenced by our calculations and a detailed analysis of the corona behavior is reported, thus revealing the key parameters in controlling the surface properties and the response of diblock copolymer modified nanoparticles.